KEBIJAKAN DIVIDEN PERBANKAN BUMN DI BEI: SEBERAPA BESAR PENGARUH LIKUIDITAS, PROFITABILITAS, DAN UKURAN PERUSAHAAN? (2018-2024) - Munawaroh, Azizatul; Sutanti, Sutanti; Lestari, Rindu Ferdina (LPPM Universitas Bina Bangsa, 2025)
This study analyzes the effect of liquidity, profitability, and company size on dividend policy in state-owned banks listed on the IDX for the period 2018-2024. The method used is multiple linear regression with panel data, processed using EViews, with a sample of four state-owned banks that meet purposive sampling. The results of the study indicate that liquidity and profitability have a positive and significant effect on dividend policy, while company size has a negative but insignificant effect. This finding indicates that banks with high liquidity and profitability are more likely to distribute larger dividends, while company size is not the main factor in dividend policy. This study provides implications for banking management to consider liquidity and profitability factors in determining dividend policy. In addition, investors are advised to pay more attention to profitability and liquidity as the main indicators in assessing a bank's dividend potential, rather than relying solely on company size.